2022
DOI: 10.1021/acsomega.2c03378
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene Nanoplastic Exposure Induces Developmental Toxicity by Activating the Oxidative Stress Response and Base Excision Repair Pathway in Zebrafish (Danio rerio)

Abstract: The widespread accumulation of nanoplastics is a growing concern for the environmental and human health. However, studies on the mechanisms of nanoplastic-induced developmental toxicity are still limited. Here, we systematically investigated the potential biological roles of nanoplastic exposure in zebrafish during the early developmental stage. The zebrafish embryos were subjected to exposure to 100 nm polystyrene nanoplastics with different concentrations (0, 100, 200, and 400 mg/L). The results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 74 publications
2
2
0
Order By: Relevance
“…Cells produce antioxidant enzymes in response to oxidative stress in vivo, and SOD is the most dominant component of antioxidant enzymes. In our study, various concentrations of 20 nm-NPs significantly reduced the activity of SOD (Figure B), which is similar to previous study that 100 nm-NPs significantly reduced the activity of SOD . Moreover, the expression level of the Cu/Zn-SOD gene showed a compensatory increase (Figure C), also illustrating that exposure to NPs causes abnormal SOD activity in oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cells produce antioxidant enzymes in response to oxidative stress in vivo, and SOD is the most dominant component of antioxidant enzymes. In our study, various concentrations of 20 nm-NPs significantly reduced the activity of SOD (Figure B), which is similar to previous study that 100 nm-NPs significantly reduced the activity of SOD . Moreover, the expression level of the Cu/Zn-SOD gene showed a compensatory increase (Figure C), also illustrating that exposure to NPs causes abnormal SOD activity in oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, various concentrations of 20 nm-NPs significantly reduced the activity of SOD ( Figure 5 B), which is similar to previous study that 100 nm-NPs significantly reduced the activity of SOD. 45 Moreover, the expression level of the Cu/Zn-SOD gene showed a compensatory increase ( Figure 5 C), also illustrating that exposure to NPs causes abnormal SOD activity in oxidative stress. Several studies have shown that MPs and NPs can cause ROS metabolism and oxidative stress in zebrafish by regulating the antioxidants of SOD.…”
Section: Discussionmentioning
confidence: 80%
“…Quantitative polymerase chain reaction (qPCR) revealed a dose-dependent upregulation of endoplasmic reticulum (ER) stress starting from day 5 onwards (Figure 2a). Consistent with Feng et al, upregulation of catalase (CAT) was observed in cells treated with 20 and 40 µg/ml NPs, suggesting an increase in oxidative stress independent of the superoxide dismutase (SOD)pathway (Figure 2a) (Feng et al, 2022). Complementing the qPCR ndings, MitoSOX assay revealed an increase in oxidative stress in a dose-dependent manner on day 5 and 7 (Figure 2b).…”
Section: Full Textsupporting
confidence: 86%
“…In accordance to these outcomes, the ecotoxicity of untreated tannery, hospital and whole tin mining effluent have been reported to cause loss in fish motility, decrease in total distance travelled and an alerting increase in frozen time (Affandi et al,2019;Chagas et al,2019;Rosales-Pérez et al,2022). These behavioural alterations were attributed to the presence of various substances explained to interfere with locomotion in aquatic species, such as heavy metals, nanoplastics, CECs such as anti-depressants (e.g., diazepam), pesticides (e.g., fenvalerate and tebuconazole), endocrine-disrupting chemicals (e.g., bisphenol A) (Ogungbemi et al,2019;Chen et al,2021;Rao et al,2022;Yao et al,2022;Feng et al,2022).…”
Section: Swfe and Jb Alter Zebrafish Swimming Behaviourmentioning
confidence: 99%